Special issue on advances in multimedia interaction and visualization - FRANCESE, Rita (2022)
Information Visualization is the field of study concerned with the development of methods for transforming abstract, complex data into visual representations in order to make that data more easily communicable and understandable. Technological advances enable information visualization in many areas, such as Visual Analytics, social media, geo-sociology, health, business, security and more. Interactivity and visualization increase the engagement with users, as they place them at the core of processes of access, dialogue, and relation with data providing visualization models for easy-to-use interactive systems. The use of interactive visualization in multimedia provides a powerful means for investigating, exploring, and imagining new communication modalities we will use in the near future. This special issue collected emerging contributions in the area of multimedia interaction and its applications for information visualization with different types of data. It includes a selection of the best papers presented at iV 2019, the 23rd International Conference on Information Visualizations. The conference took place in two different locations: 02–05 July 2019 in Paris (France) and 16–19 July 2019 in Adelaide, Australia. Participants included 70+ researchers from more than 23 countries.